Pendampingan Guru dalam Penerapan Gamifikasi Wordwall untuk Penguatan Literasi Kelautan Siswa Sekolah Dasar - Deni Wardana; Muhhamad Adam (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity was motivated by the need to strengthen ocean literacy through engaging, visual, and classroom-applicable learning media. The activity aimed to mentor teachers in using Wordwall-based gamification for introducing marine organisms to elementary school students. The method used was teacher mentoring through coordination, gamification introduction, Wordwall simulation, pre-test, teacher-led classroom practice, post-test, observation, and reflection. The teacher acted as the main facilitator and classroom controller, while the service team supported preparation, implementation, and evaluation. The partners were the classroom teacher and 15 fifth-grade students of SD Labschool UPI Serang. The results showed an increase in students’ average scores from 82.7 to 90.7, with an improvement of 8.0 points. Qualitatively, the activity encouraged enthusiasm, concept visualization, immediate feedback, healthy competition, and the need for stronger teacher instructions.